2014
DOI: 10.1016/j.neuint.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of miRNA-21 and its targets after traumatic brain injury in aging mice

Abstract: The present study investigated the possible role of miR-21, a miRNA that has known prosurvival function, in poor outcomes in the elderly following traumatic brain injury compared to adults. Controlled cortical impact injury was induced in adult (5–6 months) and aged (22–24 months) C57/BL6 mice. miR-21 and four of its targets (PDCD4, TIMP3, RECK, PTEN) were analyzed at 1, 3, 7 days post injury in samples of injured cortex using real-time PCR analysis. Basal miR-21 expression was higher in the aged brain than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 41 publications
4
24
0
Order By: Relevance
“…Several studies have reported miR-221/222 could target TIMP3 in cancers [37-39]. Besides, miR-21, miR-181, miR-373 and miR-206 could regulate TIMP3 [41-44]. It is well known that each microRNA usually has multiple target genes, and the same gene can be targeted by multiple microRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported miR-221/222 could target TIMP3 in cancers [37-39]. Besides, miR-21, miR-181, miR-373 and miR-206 could regulate TIMP3 [41-44]. It is well known that each microRNA usually has multiple target genes, and the same gene can be targeted by multiple microRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of brain remodeling and functional recovery by cell replacement effects, evidence suggests that the major effects of neurorestoration were due to the paracrine effects of secretion-based factors such as MSCs-derived exosomes that may reduce neuroinflammation, promote neurogenesis and angiogenesis, rescue pattern separation and spatial learning impairments, and improve functional recovery after TBI in animal models [107,176,178,191,204,205,215,216,[235][236][237]. In addition, as exosomes contain various miRNAs, which play a key role in modifying the phenotype and/or the physiology and modulating the cellular processes of the recipient cell, and miRNAs such as miR-21 could be potential therapeutic targets for interventions after TBI, the combination of miRNAs and MSC-derived exosomes might be a novel approach for the treatment of TBI [238]. That is, MSCs-derived exosomes that carry and transfer their cargo such as miRNAs to parenchymal cells may mediate brain plasticity and improve functional recovery after TBI [204].…”
Section: Extracellular Vesicles and Exosomesmentioning
confidence: 99%
“…More importantly, miRNAs are potential therapeutic targets in TBI. For example, miR-21, a strong prosurvival miRNA, was up-regulated in adult rat brains after TBI but down-regulated in aged rat brains after TBI [172]. A recent study manipulated the expression level of miR-21 in brain using intracerebroventricular infusion of miR-21 agomir or antagomir to evaluate the potential effect of miR-21 on neurological function in the fluid percussion injury rat model of TBI [173].…”
Section: Investigational Drugs Under Preclinical Studiesmentioning
confidence: 99%